(3GdeMGSHI GdeGdjI GdeJbOeIs - (3MSjf(B, (3GdbGVjs; (3MSjf OMOhM(B, (3QTG MeGOIs ((3YeGf(B:s (3OGQ GdKbGaI(B,s, 2007)
(3GdeMGSHIYf JhMjO GdGYeGd h EYOGO GdbhGFe GdeGdjI GdehMOI HJGQjN GdJhMjO aj Xd WQb GdeMGSHI Yf GdJhMjO h EYOGO GdbhGFe GdeGdjI HYO JGQjN JhMjO GdGYeGd , GdYedjGJ GdeJHGOdI GdeJYdbI HGdeNRhf , HGdGUhd GdKGHJI h GdeJYdbI HGdSfOGJ , GdJhMjO ZjQ GdeHGTQ eY eTcdGJ NGUI aj JhMjO GdGYeGd h CNjQG VQjHI GdONd aj JhMjO GdGYeGd (B.s
Keywords: (3GdeMGSHIs; (3GdeMGSHI(B- (3GdeGdjIs